Gamma radiation-induced mutagenesis in the development of Cavendish subgroup banana cultivars resistant to Fusarium oxysporum f. sp. cubense - Taís Ferreira Costa; Manoela Caldas Santos; Luiz Carlos de Souza Junior; Danilo Almeida Brito; Anelita de Jesus Rocha; Lucymeire Souza Morais Lino; Glaucia Amorim Faria; Claudia Fortes Ferreira; Fernando Haddad; Edson Perito Amorim; Janay Almeida dos Santos-Serejo (Euphytica, 2025)

Magnesium recovery from seawater desalination brines: a technical review - Danilo Fontana; Federica Forte; Massimiliana Pietrantonio; Stefano Pucciarmati; Caterina Marcoaldi (Environment, Development and Sustainability, 2023)
Existing desalination technologies produce large amount of waste brines with higher salinity concentration than feed seawater, the disposal of which pose serious environmental problems. At the same time, waste brines represent a valuable source of strategic materials—such as magnesium—and therefore their valorization offers the opportunity to overtake both the environmental and the economic issues. Current needs are to identify gaps and challenges to recover secondary magnesium in order to bring recovery technologies closer to the market for potential commercial applications. In this technical review, the available methods for magnesium recovery from seawater desalination brines are described and compared in details, to provide the readers with a wide overview to better address their research efforts towards resources valorization, in accordance with the circular economy principles. Graphical abstract

Active debris removal: A review and case study on LEOPARD Phase 0-A mission - Mithun Poozhiyil; Manu H. Nair; Mini C. Rai; Alexander Hall; Connor Meringolo; Mark Shilton; Steven Kay; Danilo Forte; Martin Sweeting; Nikki Antoniou; Victoria Irwin (Advances in Space Research, 2023)

Lithium iron phosphate batteries recycling: An assessment of current status - Federica Forte; Massimiliana Pietrantonio; Stefano Pucciarmati; Massimo Puzone; Danilo Fontana (Critical Reviews in Environmental Science and Technology, 2021)